REVIEW OF HOUSEHOLD BIOGAS DIGESTERS TECHNOLOGIES AND CURRENT STATUS OF ADOPTION IN BRAZIL (REMUNOM, 2025)
This article presents a narrative literature review on household biogas digester technologies and the current status of their adoption in Brazil. The research was based on scientific databases and technical reports from research institutions to consolidate dispersed information and identify key trends and challenges. The findings show that, although there have been significant advances in public, academic, and community projects, the dissemination of household biodigesters remains limited by factors such as high initial cost, lack of financial incentives, and insufficient technical support. It is concluded that the expansion of public incentive policies, training programs, and applied research is essential to strengthen this technology as an instrument for energy transition, rural sanitation, and sustainable development in Brazil.